Factorial Analysis of Tensile Properties of Areca Leaf Sheath (ALS) Subjected to Flattening - Jong, Oi-Ka; Nasharidan, Siti Adayu; Abdul Rashid, Azrin Hani; Main, Nor Mazlana; Mi, Yong Tze; Roslan, Mohd Nazrul; Masrol, Shaiful Rizal (International Journal of Integrated Engineering, 2020)
Areca leaf sheath (ALS) is a common agricultural waste produced in Southeast Asia countries, which is widely utilized over the decades to make biodegradable disposable dining wares. The workable surface of ALS for heat pressing is limited due to the concavity in the middle and folding at the edges of ALS. This study proposes that the ALS is flattened using a padding mangle prior to the forming process. The aim is to investigate the effect of ALS thickness and flattening pressure on the ultimate tensile strength and strain at break of ALS. A range of factors influencing the flattening process were investigated using design of experiment (DOE) approach based on analysis of variance (ANOVA). As the applied pressure increases, the thickness reduction of the ALS also increases. The tensile test was carried out in accordance to ASTM D3039 standard. It is found that ALS thickness and flattening pressure affect the results differently. The highest ultimate tensile strength (23.25 MPa) is obtained from 3-4 mm thick grain direction samples flattened at 5 bar; whereas the highest strain is 58.28% from perpendicular grain direction samples flattened at 1 bar, with thickness range of 3-4 mm. The results suggest that flattening process does not influence the tensile strength of ALS significantly when it is fed in parallel direction; but decreases the strain slightly.